ANALYSIS OF THE ROLE OF VILLAGE OWNED ENTERPRISES (BUMDES) IN SUPPORTING COMMUNITY EMPOWERMENT IN LAMONGAN REGENCY - Fitrotun Najiah, Evi (SEAN Institute, 2022)
This study aims to examine the role of BUMDes in improving village community empowerment, and to examine activities that can have an impact on empowering BUMDes in Jatirejo village. The selected informants are informants who know the situation and can provide reliable information about the object being studied. This study also chose key informants intentionally (purposive sampling). Data collection techniques are observation, in-depth interviews and documentation. The data analysis technique is through providing a clear description of the problem information, then interpreting it according to the results of research conducted based on theoretical support related to the object of research. While the data validity technique uses source, time, and technique triangulation. data reduction, data collection, and conclusion drawing